A CONCEPTUAL PAPER ON PRESTIGE AND ACCREDITATION AS THE KEY DETERMINANTS INFLUENCING STUDENTS’ INTENTION TO PURSUE AN ACCOUNTING COURSE - Lucy Batchy Gabriel Puem; Saifulrizan Norizan; Chan Ai Nyet; Lulu Jonathan; Tina Stephen Enggong (International Journal of Accounting, Finance and Business, 2022)
This is a conceptual paper of a future study based on the review of literature related to accounting education by the previous researchers. In response to global competitiveness in higher education, prestige and accreditation have become crucial aspects in the selection of the right programmes among university students in Malaysia. Students have to take into account many things when choosing a programme major and a career. The main objective of this study was to identify the determinants or factors affecting the intention to pursue an accounting programme. This conceptual paper went on to analyse the issues, concepts, and objectives for the forthcoming study through several literatures of various disciplines. The conceptual paper signifies supplemental literature for academics as a reference for their research. The result of this future research may provide information to the government in formulating policies that enable students to pursue accounting programmes that produce the highest number of chartered accountants in Malaysia. It is hoped that the initiatives will produce many accountants and thus expedite the countries’ aspirations of becoming fully developed nations in due time.